The impact of preceptorship on the newly qualified nurse and preceptors working in a critical care environment: An integrative literature review - Lima, Mariana Santos; Alzyood, Mamdooh (Nursing in critical care, 2024)
Background Preceptorship has been found to be effective in supporting Newly Qualified Nurses (NQNs) during their transition into challenging environments, particularly in addressing issues related to confidence and anxiety. Effective preceptorship is an element of best practice and essential to support NQNs' transition into the critical care setting. However, the impact of preceptorship on NQNs and their preceptors in critical care units is yet to be completely understood. Aim To review the impact of preceptorship on NQNs and preceptors working in a critical care environment. Study Design An integrative literature review of the literature. The review employed Whittemore and Knafl's (2005) five‐stage integrative review approach. Methods Three databases (MEDLINE, CINAHL and PsycINFO) were searched for papers published between January 2010 and May 2022. The PRISMA framework was used to guide the search and screening. Thematic analysis was used to extract, organize and analyse the data. Results Nine studies were included in this review. Reflective thematic analysis revealed three themes, with four related subthemes. Preceptorship has an impact on the development of the NQNs and preceptors' ‘nurturing’ relationship. NQNs develop their knowledge, competence and confidence when experiencing supportive preceptorship. Meanwhile, preceptors experience a combination of increased workload and opportunities for learning and professional development as a result of preceptorship. Conclusion There is evidence of the impact of preceptorship on learning and professional development for both NQNs and preceptors, but this is a complex phenomenon and further research is required to understand this area more fully. Relevance to Clinical Practice In nursing practice, it is well‐established that Newly Qualified Nurses (NQNs) often face heightened levels of anxiety and a lack of confidence when embarking on their careers, particularly in the demanding and stressful environment of critical care units. This review holds particular significance in the realm of clinical practice as it delves into the pivotal role of preceptorship in nurturing the professional growth and development of NQNs within the challenging domain of critical care. Effective preceptorship, as an essential component of best practice, plays a pivotal role in aiding NQNs' transition into critical care settings.